2011
DOI: 10.1016/j.ejcts.2011.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Pectus excavatum and pectus carinatum patients suffer from lower quality of life and impaired body image: a control group comparison of psychological characteristics prior to surgical correction

Abstract: Since self-perception is a major contributor to therapeutic decision making, a systematic evaluation of body image should be included in the assessment of patients with chest deformities. Body image concerns may be even more relevant to the decision-making process than physical restrictions. Exaggerated dysmorphic concerns should be prospectively investigated in their ability to influence the extent of satisfaction with the surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
110
2
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(131 citation statements)
references
References 18 publications
6
110
2
13
Order By: Relevance
“…Similarly, Krasopoulos et al have reported a statistically significant improvement in the self-esteem of pectus deformity patients after having undergone reparative surgery (p = 0.001) [24]. Steinmann et al proposed that body image concerns may overshadow those of the presence of physical restrictions when ultimately deciding whether or not to repair pectus deformities, as patients' perceptions of their dysmorphia will ultimately influence the extent of satisfaction with treatment outcomes [25].…”
Section: Indications For the Treatment Of Pectus Deformitymentioning
confidence: 99%
“…Similarly, Krasopoulos et al have reported a statistically significant improvement in the self-esteem of pectus deformity patients after having undergone reparative surgery (p = 0.001) [24]. Steinmann et al proposed that body image concerns may overshadow those of the presence of physical restrictions when ultimately deciding whether or not to repair pectus deformities, as patients' perceptions of their dysmorphia will ultimately influence the extent of satisfaction with treatment outcomes [25].…”
Section: Indications For the Treatment Of Pectus Deformitymentioning
confidence: 99%
“…В этот период за несколько месяцев в связи с ро-стовым скачком минимальный ранее косметиче-ский дефект становится грубым и уродующим [2], что может сильно повлиять на всю последующую жизнь. Именно поэтому в настоящее время показа-ниями к оперативному лечению являются не только функциональные изменения со стороны сердечно-сосудистой и дыхательной систем, но и грубый кос-метический дефект, который существенно влияет на качество жизни пациента [1,13,14,16,17].…”
unclassified
“…PE may also impair restrict chest wall movement and impair cardiorespiratory function (3)(4)(5). Patients report symptoms related to the deformity as exercise intolerance, shortness of breath, and weakness (2,6,7). Previously, it has been stated that the deformity did not cause physiological dysfunction (1,2).…”
Section: Introductionmentioning
confidence: 99%